2015
DOI: 10.1007/s10499-015-9909-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial replacement of fish meal with Spirulina platensis meal in practical diets on growth, survival, body composition, and reproductive performance of three-spot gourami (Trichopodus trichopterus) (Pallas, 1770)

Abstract: This study investigated the effects of fish meal replacement by Spirulina platensis meal on growth, survival, body biochemical composition, and reproductive performance of Trichopodus trichopterus until the first spawning for 16 weeks. The fish fed dietary algal meal at levels of 2.5, 5, 10, and 20 % against those received fish meal only as control. The results showed that indicators such as belly diameter, feed intake, feed conversion ratio (FCR), and viscerosomatic index were significantly different between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 33 publications
6
27
0
1
Order By: Relevance
“…This supports to one finding of Jaime‐Ceballos, Villarreal, Garcia, Perez‐Jar, and Alfonso () where the survivability of white shrimp Litopenaeus schmitti was around 80% when spirulina platensis was included in microdiets. Khanzadeh, Fereidouni, and Berenjestanaki () studied on juvenile Trichopodus trichopterus and also reported higher survival rates (93%–100%) of the juvenile T. tricopterus fed diets of 2.5 and 10% Spirulina platensis meal.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This supports to one finding of Jaime‐Ceballos, Villarreal, Garcia, Perez‐Jar, and Alfonso () where the survivability of white shrimp Litopenaeus schmitti was around 80% when spirulina platensis was included in microdiets. Khanzadeh, Fereidouni, and Berenjestanaki () studied on juvenile Trichopodus trichopterus and also reported higher survival rates (93%–100%) of the juvenile T. tricopterus fed diets of 2.5 and 10% Spirulina platensis meal.…”
Section: Discussionmentioning
confidence: 94%
“…was around 80% when spirulina platensis was included in microdiets. Khanzadeh, Fereidouni, and Berenjestanaki (2016)…”
Section: Colour Measurement In Experimental Diets and Fishmentioning
confidence: 99%
“…Bairagi et al (2004) suggested the possible incorporation of Leucaena leaf meal inoculated with fish intestinal bacteria in rohu diet up to 40%. Given the relative enhancement of growth parameters and significant improvement in reproductive performance of broodstock threespot gourami, 8.1-9.6% S. platensis meal instead of fish meal is recommended in the diets (Khanzadeh et al, 2016). The effect of Spirulina platensis as feed supplement for growth and alternative natural carotenoid source (Teimouri et al, 2016) was studied in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, it can be used as a source of protein and a strong immune stimulant in the diet without impairing fish growth (Andrews, Sahu, Pal, Mukherjee, & Kumar, 2011). Improvement in feed digestibility, digestive enzymes, pigmentation, blood chemical and haematological parameters, lipid peroxidation and growth performance; enhancing immune response and stress response; and increasing fillet content of omega-3 fatty acids have been previously reported as benefits of spirulina supplementation (Cao et al, 2018;Gogoi, Mandal, & Patel, 2018;Jafari et al, 2014;Khanzadeh, Fereidouni, & Berenjestanaki, 2016;Lin et al, 2016;Palmegiano et al, 2008;Sarker, Gamble, Kelson, & Kapuscinski, 2016;Tan, Galaz, & Shapawi, 2017;Teimouri, Amirkolaie, & Yeganeh, 2013;Teimouri, Yeganeh, & Amirkolaie, 2016;Velasquez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%